Developmental Sequences in Second Language Phonology: Effects of Instruction on the Acquisition of Foreign sC Onsets - Cardoso, Walcir; Collins, Laura; Cardoso, Walciléa (Frontiers in Communication, 2021)
This study investigates the effects of three types of instruction on the acquisition of foreign /s/-initial onset clusters (/sl/, /sn/, and /st/ - sC clusters), a process characterized by a developmental sequence in which /sl/ is acquired before /sn/ and /st/. 118 native speakers of Brazilian Portuguese participated in a four-week language course to learn a set of vocabulary and associated pronunciation of Taki, a self-constructed miniature linguistic system. The participants were divided into three groups, each corresponding to one of the hypotheses that characterize three types of explicit second language instruction: Teachability (Pienemann, 1984, 2007), Projection of Markedness (Projection; Zobl, 1983), and a combination of the two (Mixed; Lightbown, 1998). A mixed ANOVA analysis of the participants’ production of sC clusters revealed that, in one of the tasks employed (read aloud), the group that focused exclusively on the more marked /st/ (Projection Group) had the best overall performance in the acquisition of the three clusters: this group was able to generalize their knowledge to the sC clusters they were not taught. In general, the results support Zobl’s (1983) Projection Model of Markedness for explaining the phonological development of syllable structure, wherein the instructional effect of a focus on the most marked /st/ projects to knowledge of the less marked structures.